Self-care in type 2 diabetes and its relationship with sex, age, adherence, health habits and knowledge (UNED Research Journal, 2025)
Introduction: Type 2 diabetes is a chronic condition with high prevalence and significant impact on quality of life. Self-care practices are essential to prevent complications, particularly among working populations. Objective: To identify self-care practices among employees of a public university in Costa Rica diagnosed with type 2 diabetes. Methods: An online survey was administered between June and October 2024 to individuals with a confirmed diagnosis of type 2 diabetes (n=111). The questionnaire explored behaviors related to diet, physical activity, treatment adherence, foot care, and disease knowledge. Results: Women reported greater engagement in self-care behaviors and demonstrated higher levels of knowledge about the condition. Participants aged 50 years and older showed higher adherence to treatment and more consistent medical follow-up. Conclusion: Strengthening self-care promotion strategies targeted at employees with type 2 diabetes under 50 years of age and men is a priority for preventing complications and supporting long-term disease management.
Keywords: type 2 diabetes; self-care; health promotion; lifestyle; occupational health